EKSTRAKSI DAN KARAKTERISASI INULIN DARI UMBI DAHLIA (Dahlia sp.L) SEGAR DAN DISIMPAN - Hevi Horiza; Minda Azhar; Jon Efendi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
Inulin is a natural polymer composed of monomers fructose, which is connected with the linear bonding ?-2,1-fruktosil-fructose. One source of inulin is the dahlia tubers (65.700%). The purpose of this study was to determine the water content, degree of purity inulin and how the value of the degree of polymerization inulin from dahlia tubers fresh and stored 4 weeks kinds of decorative strands formal crimson crown. This research was conducted experiments in Chemistry Research Laboratory UNP. The object of research was a kind of decorative dahlia tubers formal crimson obtained in the area of Aia Tawa, Kampung Batu nature, Solok. Inulin was characterized by using GC (Gas Chromatograpy) and HPLC(High-PerformanceLiquidChromtography). Determination of water content by using method of the AOAC(Associationof Official of Analytical Chemist).The results showed that the water content of dry weight percent (bk) inulin from dahlia tubers fresh is 2.123%, Inui figure is not much different than the inulin from dahlia tubers stored 4 weeks 2.003%. Based on the GC spectrum can be analyzed qualitatively that inulin extracted from dahlia tubers have a degree of polymerization of smaller than commercialinulin. Chicory Based on the spectrum of HPLC showed that inulin extracted from the tubers of dahlias has a purity level is almost the same as inulin commercial Chicory merck Fluka.